Dislocated hybrid synchronization via. tracking control & parameter estimation methods with application. (2nd November 2021) - Khan, Ayub; Trikha, Pushali; Seth Jahanzaib, Lone
ABSTRACT: In this article the dislocated hybrid synchronization between chaotic systems of different structures viz. real integer order and complex fractional order have been performed using two control methods viz. tracking control method and parameter estimation adaptive method. Illustrative example of the application of synchronization in secure communication has been performed. Numerical simulations have been performed using MATLAB which verify the efficacy of both the methods and help compare results.